Understanding productivity in maternity wards - Marina Di Giacomo; Massimiliano Piacenza; Luca Salmasi; Gilberto Turati (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2024)
This paper provides a causal estimate of labor productivity in maternity units. We consider an Italian law that defines the staffing requirements of maternity wards according to the annual number of births. We exploit these discontinuities in the availability of medical staff induced by the law to define both instrumental variables and an RDD framework that allows us to estimate the causal effect of different teams of professionals during delivery on the health status of newborns and mothers. The analysis is based on detailed patient-level data on deliveries in an Italian region. We find that maternity units with annual births above the thresholds are more likely to have a "full team" of professionals during delivery. In turn, the presence of a full team significantly affects outcomes. We find an improvement in both neonatal and maternal outcomes, coupled with more intense use of medical procedures, suggesting that larger hospitals are better able to manage deliveries with appropriate treatments to avoid complications than smaller units. In addition, we do not find substantial heterogeneous effects across days of the week, time of day, and nationality of mothers.
Keywords: D24; H75; I10; I12; I18; J24; J45; J82; 330; medical staff; maternity wards; productivity; instrumental variables